1991
DOI: 10.2105/ajph.81.6.703
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial to evaluate the risk of gastrointestinal disease due to consumption of drinking water meeting current microbiological standards.

Abstract: BACKGROUND: This project directly and empirically measured the level of gastrointestinal (GI) illness related to the consumption of tapwater prepared from sewage-contaminated surface waters and meeting current water quality criteria. METHODS: A randomized intervention trial was carried out; 299 eligible households were supplied with domestic water filters (reverse-osmosis) that eliminate microbial and chemical contaminants from their water, and 307 households were left with their usual tapwater without a filte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
205
3
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(219 citation statements)
references
References 11 publications
10
205
3
1
Order By: Relevance
“…The estimate of population incidence rate was lower than that found in studies in the US and Canada [10,11] but was similar to that found in the Dutch study (their case definition required symptoms to last over 24 h) [9]. The presentation rate to GPs was similar to that found in GP studies in the UK in the early 1980s [5,6] and in the recent Dutch study [9], but were lower than the most recent general practice morbidity statistics [12].…”
Section: Discussioncontrasting
confidence: 64%
“…The estimate of population incidence rate was lower than that found in studies in the US and Canada [10,11] but was similar to that found in the Dutch study (their case definition required symptoms to last over 24 h) [9]. The presentation rate to GPs was similar to that found in GP studies in the UK in the early 1980s [5,6] and in the recent Dutch study [9], but were lower than the most recent general practice morbidity statistics [12].…”
Section: Discussioncontrasting
confidence: 64%
“…[3][4][5][6][7][8][9] Contaminated municipal water supplies have been implicated in disease transmission in diarrheal outbreaks around the world. 6,[8][9][10][11][12][13] However, few studies to date have evaluated the burden and routes of transmission of enteric diseases in relatively developed countries with suboptimal sanitary infrastructure, such as the newly independent Central Asian States. Our analysis of disease transmission in Nukus reveals that in this case the endemic disease burden is caused primarily by contaminated public water supply rather than by poor sanitation, poor hygiene practices, or other causes.…”
Section: Discussionmentioning
confidence: 99%
“…12 Individuals with access to piped water at their residence experience fewer episodes of diarrheal disease than those without access to piped water. Nonetheless, drinking home-chlorinated water results in lower diarrheal incidence than drinking the piped water provided in Nukus.…”
Section: Discussionmentioning
confidence: 99%
“…HCGI was defined as having three or more loose, watery stools within a 24-hour period, blood in the stool, and/or vomiting using a 2-day recall period. 19,20 The remaining eligible households comprised of 51 spatially coherent household clusters with a mean cluster size of 10 households. A random number was then assigned to each household and sorted in ascending order, first by the random number and then by cluster number.…”
Section: Methodsmentioning
confidence: 99%